2023
DOI: 10.37201/req/074.2022
|View full text |Cite
|
Sign up to set email alerts
|

Validity and usefulness of the RAE-CMBD studying patients hospitalised with influenza

Abstract: Background. Understanding the hospital impact of influenza requires enriching epidemiological surveillance registries with other sources of information. The aim of this study was to determine the validity of the Hospital Care Activity Record – Minimum Basic Data Set (RAE-CMBD) in the analysis of the outcomes of patients hospitalised with this infection. Methods. Observational and retrospective study of adults admitted with influenza in a tertiary hospital during the 2017/2018 and 2018/2019 seasons. We calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, we considered that our definition of influenza hospitalization was very specific, as we assumed that the attribution of an ICD-10 influenza code relies on a viral confirmation test as per guideline recommendations. However, the SNSSHD used in this study, which has been validated for influenza infection in Spain ( 31 ), showed 79.87% sensitivity, 99.72% specificity, 86.71% positive predictive value and 99.54% negative predictive.…”
Section: Discussionmentioning
confidence: 68%
“…However, we considered that our definition of influenza hospitalization was very specific, as we assumed that the attribution of an ICD-10 influenza code relies on a viral confirmation test as per guideline recommendations. However, the SNSSHD used in this study, which has been validated for influenza infection in Spain ( 31 ), showed 79.87% sensitivity, 99.72% specificity, 86.71% positive predictive value and 99.54% negative predictive.…”
Section: Discussionmentioning
confidence: 68%
“…We obtained anonymized individual-level data on daily hospitalizations from the Ministry of Health’s national hospital discharge database (“Conjunto Mínimo Básico de Datos”, CMBD) that reports more than 90% of all admissions in both public and private institutions [ 35 ] and has been validated for data quality [ 36 , 37 ]; and mortality data from the National Statistical Office’s mortality database (“Base de datos de mortalidad del Instituto Nacional de Estadística”, BDM) that reports 100% of deaths [ 38 ] between 2016 and 2019. All diagnoses were coded according to the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) [ 39 ].…”
Section: Methodsmentioning
confidence: 99%